INTEGRASI ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN AGAMA ISLAM: ANTARA RISIKO COGNITIVE DEBT DAN PENGUATAN KESADARAN KOLEKTIF UMAT - Hakim, Faisol (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the integration of Artificial Intelligence (AI) in Islamic Religious Education (IRE/PAI) with a focus on three interrelated dimensions: pedagogical opportunities, the risk of cognitive debt, and implications for the collective consciousness of the Muslim community. Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this research analyzed literature retrieved from six reputable databases Scopus, Web of Science, ERIC, DOAJ, Dimensions, and Google Scholar covering publications from 2013 to 2025. From an initial pool of 122 articles, 39 relevant studies were selected through a staged screening process, with ten Scopus-indexed articles designated as core primary studies. Thematic analysis identified five major clusters: pedagogical utility, algorithmic limitations, cognitive debt, affective deficits, and ethical-collective consciousness frameworks. Findings confirm that while AI enhances instructional efficiency and accessibility particularly in Qur'anic learning and institutional management uncontrolled usage generates cognitive debt, weakens reflective capacity, and creates affective deficits that undermine the teacher's irreplaceable role as murabbi. This study concludes that AI integration in IRE must be grounded in an ethical framework derived from Maqāṣid al-Sharī'ah, particularly the principles of Hifz al-Aql and Hifz al-Din, to safeguard intellectual integrity and strengthen Muslim collective consciousness in the digital era,